Narratividade e figurativização em dois videoclipes d’O Rappa - Ardenghe, Cláudia Cristina Cabral (2012)
This research aims to clarify the applicability of greimasiana semiotic theory in the classroom as a pedagogical tool to encourage reading and writing to high school students. The research comes from the experience of this researcher with the teaching of courses Literature, Language and Writing in Portuguese high-school grades, which realizes the high resistance to reading by the students, especially in relation to literary works. Thus, the aim is not to teach French semiotics of online students, but select, within the theory, key concepts (some already widespread in textbooks of literature and writing) that allow them to improve the practice of reading. The following factors were taken the concepts of narrative and Route Scheme generative of meaning, especially the level of discourse, the figurative and thematic routes, and mood. It is taken here as corpus analysis, video, text type that runs away, purposely, the traditional approach in the classroom in which they work primarily with the canonical genres. The video then appears as an object of an innovative pedagogical practice, in terms of teaching practice and at the same time, familiar to students, since the audiovisual text occupies a large space, mainly thanks to the internet (You tube, for example) in the lives of children, adolescents and young adults. Furthermore, the insertion of the video in the classroom will meet the assumptions of the National Curriculum for secondary education, as it leads to the classroom new media, offers a discussion of concepts such as art or literariness, while still allowing a reflection of a social nature, as is the case here. Thus, it is believed, with this choice, the analysis of the video - gender syncretic in nature, blending sound, image, lyrics and melody - may increase, at first, the possibility of interaction of students with the discipline of Language Portuguese, since: (1) the short length of the body allows them to read it or know it for a single class, not requiring the read at home, that is, the practice of students' reading changes, (2) the relationship between image and words can be easily exploited, allowing you to study the common and distinct aspects of the lyrics and video images (the different routes narrative, figurative and thematic are drawn), exposing students to the complex nature of meaning; (3) the teacher takes on a different role in the interaction with students, in close proximity, since instead of dealing with an object that does not always belong to the universe of young people, is an object that is part of their daily lives and your imagination. In a second step, it is believed that having already motivated students and give them some rudiments of semiotic analysis that can improve your reading, be more productive return to purely verbal texts, literary or not, and develop well, the practice of interpretation and production of texts in the classroom. For this research, in general, were chosen videos group O Rappa, band of notorious appeal to young people deal with social issues (exclusion, poverty, racism) and have influences from several genres (funk to MPB).